Network neuroscience of apathy in cerebrovascular disease. (May 2020) - Tay, Jonathan; Lisiecka-Ford, Danuta M.; Hollocks, Matthew J.; Tuladhar, Anil M.; Barrick, Thomas R.; Forster, Anne; O'Sullivan, Michael J.; Husain, Masud; de Leeuw, Frank-Erik; Morris, Robin G.; Markus, Hugh S.
Highlights: A network-based model may be able to describe apathy in cerebrovascular disease. Focal network damage, such as in stroke, could lead to network failure and apathy. Changes to remote regions or network disconnection can lead to apathy over time. Specific subnetworks may underlie motivation-related cognitive functioning. Understanding the network basis of apathy could lead to targeted treatments. Abstract: Apathy is a reduction in motivated goal-directed behavior (GDB) that is prevalent in cerebrovascular disease, providing an important opportunity to study the mechanistic underpinnings of motivation in humans. Focal lesions, such as those seen in stroke, have been crucial in developing models of brain regions underlying motivated behavior, while studies of cerebral small vessel disease (SVD) have helped define the connections between brain regions supporting such behavior. However, current lesion-based models cannot fully explain the neurobiology of apathy in stroke and SVD. To address this, we propose a network-based model which conceptualizes apathy as the result of damage to GDB-related networks. A review of the current evidence suggests that cerebrovascular disease-related pathology can lead to network changes outside of initially damaged territories, which may propagate to regions that share structural or functional connections. The presentation and longitudinal trajectory of apathy in stroke and SVD may be the result of these network changes. Distinct subnetworks might support cognitive components of GDB, the disruption of which results in specific symptoms of apathy. This network-based model of apathy may open new approaches for investigating its underlying neurobiology, and presents novel opportunities for its diagnosis and treatment.